Hypothyroidism and stunting around the Merapi Volcano - Pramudji Hastuti; Ahmad Hamim Sadewa; Prasetyastuti -; Sunarti -; Arta Farmawati; Ngadikun -; Dianandha Septiana Rubi; Abrory Agus Cahya Pramana (Journal of Community Empowerment for Health, 2021)
Cangkringan is a mountainous area with the possibility of low iodine sources in the soil. Additionally, Cangkringan area is the area nearest to where eruptions of Merapi mountain have occurred, which further could reduce iodine levels in the soil. This study examined the incidence of hypothyroidism due to iodine deficiency and potential links to stunting events on the slopes of Merapi mountain. By using ELISA methods, a total of 97 mothers were tested to detect the triiodothyronine (T3) and thyroid-stimulating hormone (TSH) levels to determine the frequency of hypothyroidism, while 97 children were assessed to check the stunting rates by measuring height compared to age. We found hypothyroidism was 3 (3.1%) out of 97 mothers examined and 30 (30.9%) out of 97 children examined were stunted (18.5% short stature and 12.4% very short stature). There was a significant difference between the mothers’ TSH levels among very short stature and normal stature. We concluded that hypothyroidism in mothers is correlated with stunting children in Cangkringan, Sleman sub-district. Further research is needed to determine the frequency of hypothyroidism and stunting in other slopes of Merapi mountain, where the low-iodine soil composition is potentially related to hypothyroidism and stunting incidence. Thus, further treatment is needed by local health staff and governments to address the negative effects of hypothyroidism and stunting.